Anti-interleukin-6 receptor antibody prevents systemic bone mass loss via reducing the number of osteoclast precursors in bone marrow in a collagen-induced arthritis model. (3rd January 2014) - Tanaka, Keisuke; Hashizume, Misato; Mihara, Masahiko; Yoshida, Hiroto; Suzuki, Miho; Matsumoto, Yoshihiro
Summary: Systemic bone loss is a hallmark of rheumatoid arthritis (RA). Inflammatory cytokines such as interleukin (IL)-6 promote bone resorption by osteoclasts. Sphingosine-1-phosphate (S1P) controls the migration of osteoclast precursor cells (OCPs) between the blood and bone marrow, in part via S1P receptors (S1PR1 and S1PR2) expressed on the surface of OCPs. OCPs (CD11b + Gr-1 low+med ) isolated from bone marrow of DBA/1J mice were stimulated with IL-6. S1P-directed chemotaxis of OCPs was evaluated using a transwell plate. mRNA expression of S1PR1 and S1PR2 was measured. DBA/1J mice were immunized with bovine type II collagen (days 0 and 21) and anti-mouse IL-6 receptor antibody (MR16-1) was administered on days 0 and/or 21. Trabecular bone volume was analysed using micro-computed tomography. The percentage of OCPs in tibial bone marrow and S1PR1 and S1PR2 mRNA expression in OCPs were measured. IL-6 stimulation significantly decreased S1P-directed chemotaxis of OCPs. IL-6 induced S1PR2 mRNA expression, but not S1PR1 mRNA expression, in OCPs. Bone volume was significantly lower in arthritic mice than in non-arthritic control mice on day 35. Treatment of immunized mice with MR16-1 significantly inhibited bone loss. In MR16-1-treated mice, the percentage of OCPs and expression of S1PR2 mRNA was each decreased compared with arthritic mice on day 14, but not on day 35. IL-6 increased the number of OCPs in tibial bone marrow via up-regulating S1PR2, thus playing a crucial role in systemic bone loss induced by inflammation.